CARIES DENTAL EN ADULTOS JÓVENES Y SU RELACIÓN CON LA RESPUESTA INMUNE SECRETORIA DE LA MUCOSA BUCAL Y NEUROENDOCRINO SUPRARRENAL. DIFERENCIAS EN EL GÉNERO - Pautasso, Rita; Liliana, Recchioni; Patricia, Cordoba (European Scientific Journal, ESJ, 2014)
Introduction: In daily life people are exposed continuously to environmental stimuli that provoke adaptation responses that modify internal physiological mechanisms leading to some diseases. Processes related to stress have been widely studied; however, the relationship between dental health with adrenal endocrine and immunological responses, has received very little attention. Objective: The purpose of the present study was to establish the possible relationship between dental status and two physiological defense mechanisms, such as the immunological secretory activity of the oral mucosa, and the adrenal glands response. Materials and Methods: Forty young adults (mean age 28.6 and standard deviation of ± 2.4 year old) were selected and divided into two groups; Group 1 (Control, n = 20) with basal dental status of ≤ 1 cavity; and Group 2 (Cavities, n = 20) with a basal status of ≥ 7 cavities. In addition, 4 additional subgroups were formed; Group 1a (n = 10) having only males; Group 1b (n = 10) having only females; Group 2a (n = 10), males, and Group 2b (n = 10), females. Variables measured as secretory immune activity index were: (1) total immunoglobulin determined in saliva by simple radial immunediffusion; and (2) anti-Streptococcus mutans immunoglobulin A (IgA anti Sm) determined by ELISA. Variables measured as endocrine activity index were: (3) Urine adrenalin, determined by High Pressure Liquid Chromatography, and (4) cortisol, determined by RIA. Urine and cortisol determinations were made in 24 h recollection samples. Statistical comparisons by group and subgroups were made by ANOVA. A p < 0.05 was considered significant. Results: Comparisons between Group 2a versus Group 2b (males Vs. females, Caries group) showed that both total IgA and adrenaline were significantly higher in males than in female subjects (p < 0.01, and p < 0.05). Group 2a also had IgA and adrenaline levels significantly higher than Groups 1a and 1b ( p < 0.05 and p < 0.01). Comparisons between Group 2a versus Group 1 (Control) showed significantly lower concentration of IgA antiSm (p < 0.05). Comparisons between Groups 2a and 2b, showed a significant lower concentration of cortisol in female subjects (p < 0.05). The same situation was observed when Group 2b was compared with Group 1b (p < 0.05). Conclusions: Results suggest significant differences in the dental status of male and female subjects. There is an apparent relationship between the dental status and a higher adrenal activation in males bearing a greater proportion of cavities. Interestingly, this endocrine response is not followed by an increased concentration of the IgA antiSm. Cavities in the Group 2b (female subjects) suggest a diminished activity of the hypothalamic-corticoadrenal axis.